Gratitude and Self Efficacy on the Subjective Well-being of Kindergarten Teachers - Agustina Sativa Poima; Yulia Ayriza (Universitas Ahmad Dahlan, 2024)
Heavy workload of kindergarten teachers is the main of their work pressure can cause physical and emotional fatigue as well as decreased job satisfaction. Therefore, it is important to consider the subjective well-being of kindergarten teachers. This study aims to determine the effect of gratitude and self-efficacy on subjective well-being among kindergarten teachers. This study used 128 sample of kindergaren teachers that measured by The Gratitude Questionnaire-6 (GQ-6), General Self-Efficacy Scale, Satisfaction with Life Scale (SWLS) and the PANAS Scale. The finding reasearch is both gratitude and self-efficacy have a positive impact on the subjective well-being of kindergarten teachers.